Significance of Holter Monitoring in Evaluation of Non-Specific Symptoms - Mohammad Nadeem (Journal of Rawalpindi Medical College, 2012)
Background: To determine the diagnostic significance of Holter monitoring in evaluation of non-specific symptoms (like palpitations, dizziness, syncope,etc.). Methods: In this descriptive study 100 consecutive patients referred for the evaluation of non-specific symptoms were selected for Holter monitoring after initial evaluation. Through Holter monitoring two channels via five leads, placed over the anterior chest wall, were recorded. The disc was attached to a strap, which the patient wore on his shoulder. The recording was usually started in the morning at hospital and the patient was allowed to resume his normal activities. He was advised to maintain his activity log and asked to report back at the same time next day. Results: Ventricular ectopics less than 10% were present as isolated events in 81%. Supraventricular episodes less than 10% were present as isolated events in 93%.Mean minimum heart rate was 43 , mean maximum heart rate was 123 and mean average heart rate was 71 . The ST-segment shift was present in 21% of the population in which 3% were ST-segment elevation and 19% were STsegment depressions. Conclusion: For the patients with non-specific symptoms Holter monitoring has got an insignificant role, in the primary diagnosis of myocardial ischemia or arrhythmia as a cause of such symptoms.